Intracranial solitary fibrous tumor/hemangiopericytoma: Role and choice of postoperative radiotherapy techniques - Gou, Qiheng; Xie, Yuxin; Ai, Ping (Frontiers in Oncology, 2022)
Background: Intracranial solitary fibrous tumor/hemangiopericytoma (SFT/HPC) is a novel rare disease after the 2016 WHO reclassification. Surgery is the main treatment. Postoperative adjuvant radiotherapy is often used, but the effects of different radiotherapy techniques are still unclear. The purpose of this study was to analyze the effects of postoperative radiotherapy (PORT) and different radiotherapy methods on the efficacy of patients with intracranial SFT/HPC. Materials and methods: We retrospectively analyzed 42 patients with intracranial SFT/HPC who underwent surgical treatment from 2008 to 2022, 20 of whom were treated with postoperative intensity-modulated radiotherapy (IMRT) and 22 with postoperative stereotactic radiosurgery (SRS). The Kaplan–Meier method was used to analyze the disease-free survival (DFS) of all the 42 patients receiving postoperative radiotherapy and the time to progression (TTP) of 22 of these patients experiencing recurrence. A multivariate Cox proportional hazards model was used to detect prognostic factors of survival. Results: In the analysis of PORT patients, the median DFS was 8.33 years for PORT IMRT patients and 3.04 years for PORT SRS patients. The 10-year DFS incidence was 46.0% in the PORT IMRT group and 27.5% in the SRS group. Among the 22 patients who relapsed, the median TTP of other patients was 1.25 years, of which 3 received radiotherapy alone and 1 received symptomatic treatment, while the median TTP of surgical and surgical combined with radiotheray patients were 1.83 and 2.49 years, respectively (p=0.035). Conclusion: PORT IMRT could prolong DFS compared with PORT SRS. It indicated that PORT IMRT radiotherapy technology was a feasible option for SFT/HPC. Moreover, TTP results of relapsed patients showed that,surgery and surgery combined with radiotherapy treatments have no significant difference on TTP in relapsed patients, but both of them were better than other treatments.